Prevalence and Associated Factors of Psychological Distress of Patients with Stroke Attending a Neurology Clinic — An Analytical Cross-sectional Study - Weerasekara, Pumudu; Warshawithana, Chalitha; Weerasinghe, Nelushi; Mashood, Irshad (International Journal of Medical Students, 2024)
Background: A vast range of factors lead to psychological distress among stroke patients, causing poor outcomes. This study aimed to assess the prevalence of psychological distress and identify the associated factors among stroke patients attending the Neurology Clinics of the National Hospital of Sri Lanka (NHSL), Colombo. Methods: A descriptive cross-sectional study with an analytical component was conducted among 177 patients with stroke attending the Neurology Clinics of the NHSL, Colombo, who were sampled by multistage random sampling. Psychological distress was assessed using the Kessler Psychological Distress Scale (K-10). Data collected under 6 domains underwent initial bivariate analysis using Chi-square and Fisher’s Exact Tests, followed by multivariate analysis via binary logistic regression. Results: The mean age of the participants with stroke was 59.7 (SD:12.3) years. The prevalence of psychological distress among stroke patients was found to be 23.3% (95% CI:16.1–31.9). During bivariate analysis, six factors (p<0.05) were significant. The regression analysis identified five independent predictors: younger age (OR =0.87, 95% CI=0.79–0.97, p<0.05), female gender (OR=70.94, 95% CI=3.73–1348.89, p=0.05), patient being the sole source of income (OR=24.71, 95% CI=1.67–362.01, p<0.05), increased level of disability (OR=13.05, 95% CI=3.59–47.36, p<0.001), and past personal history of psychiatric disorders (OR=172.59, 95% CI=3.64–8174.42, p<0.05) with a R2 of 0.772. Conclusion: The prevalence of psychological distress among patients with stroke attending the Neurology Clinics of the NHSL, Colombo, is considerably high and is associated with multiple health and non-health related factors.